Syndrome of inappropriate antidiuretic hormone secretion following extensively drug-resistant Klebsiella pneumoniae associated with complicated urinary tract infection: a case report - Li, Junqing; Yang, Zhuo; Wang, Kai; Zha, Bingbing; Du, Yong; Shi, Jindong; Jie, Zhijun; Ding, Heyuan (Frontiers in Medicine, 2025)
Hyponatremia is strongly associated with syndrome of inappropriate antidiuretic hormone secretion (SIADH). We present an 82-year-old male with refractory hyponatremia unresponsive to the discontinuation of hydrochlorothiazide and comprehensive treatment (fluid restriction, sodium supplementation, and tolvaptan). Two consecutive urine cultures identified extensively drug-resistant Klebsiella pneumoniae (XDRKP). After tigecycline treatment, serum sodium returned to normal and remained stable during one-year follow-up. This case suggests a close relationship between XDRKP infection and SIADH, highlighting the need to evaluate drug-resistant pathogens in patients with refractory hyponatremia and the importance of antimicrobial therapy in the management of electrolyte disorders secondary to drug-resistant urinary tract infections.